Mechanism-based thermodynamic analysis for one-step and two-step ethanol-to-1,3-butadiene conversion processes - Rahman, Md Ziyaur; Varma, Abhishek R.; Gadkari, Siddharth; Tawai, Atthasit; Sriariyanun, Malinee; Kumar, Vinod; Maity, Sunil K. (American Chemical Society, 2024)
Renewable 1,3-butadiene (BD) is essential for sustainability of the synthetic rubber sector. This work presents a comprehensive thermodynamic analysis for one- and two-step ethanol-to-BD conversion processes. The two-step process comprises ethanol dehydrogenation, followed by the condensation of acetaldehyde with another ethanol molecule into BD. The process involves a complex reaction network with a wide range of byproducts depending on the nature of the catalysts and operating conditions, lacking unique consensus on the C-C bond-forming mechanism. This study elucidates the temperature regime for the spontaneity of the reactions proposed in various mechanisms and side reactions based on the standard Gibbs free energy change. The equilibrium conversion and product selectivity were further calculated under a wide temperature and pressure range. The overall reaction in the one-step process is thermodynamically spontaneous above 417 K, while the first and second steps of the two-step process are spontaneous above 550 and 285 K, respectively. Excepting Prins condensation, other mechanisms lack the spontaneity of all reaction steps. The equilibrium BD selectivity is favorable at elevated temperatures and low pressures. The addition of acetaldehyde in the two-step process has a favorable impact with higher BD selectivity, the maximum being at a 1:1 molar ratio of ethanol/acetaldehyde. This study elucidates thermodynamic insights into existing mechanisms and drives the evolution of a feasible mechanism. This effort will eventually help design novel catalysts and optimized processes for sustainable biobased BD production using ethanol derived from renewable feedstocks, aligning with the global commitment to greener and resource-friendly chemical manufacturing.
Keywords: 40 Engineering; 4002 Automotive Engineering; 7 Affordable and Clean Energy; 12 Responsible Consumption and Production; Chemical Engineering; 34 Chemical sciences